Determinants Of The Use Of Tic Information Technologies By Entrepreneurs In The Hassi Messaoud Region By Using The Technology Acceptance Model Tam - Mezaour, Amel; Chadli, Chaouki (جامعة الوادي - University of Eloued, 2022)
This research paper aims at a descriptive study on the use of information and communication technologies (TIC) by small and medium enterprises that are active in the Hassi Messaoud region in the field of technology (networks, optical fibers and applications) using the technology acceptance theory (TAM), and to test the extent of the influence of external determinants on the model from Through two main determinants (perceived ease of use and perceived usefulness of use), the questionnaire tool was used to collect data that was distributed to 58 institutions, and 28 of them were retrieved and studied, and 28 were valid for testing. strong among external determinants (efficiency of using technologies, Gaining time due to use, government subsidies, complexity) and model limitations (TAM) This confirms the existence of an influencing relationship between external determinants and the use of information technologies by SME in the Hassi Messaoud region.
مقال
Keywords: TAM Model, ICT, SME.Perceived ease of use, Perceived usefulness.